A retrospective study of patients with follicular lymphoma (FL): identification of in situ FL or FL-like B cells of uncertain significance in lymph nodes resected at the time of previous surgery for carcinomas. Issue 7 (10th April 2015) - Morita, Kohei; Nakamine, Hirokazu; Nakai, Tokiko; Takano, Masato; Takeda, Maiko; Enomoto, Yasunori; Yoshii, Yumi; Kanno, Masatoshi; Ohbayashi, Chiho
Abstract : Background and aims: In situ follicular lymphoma (iFL)/intrafollicular neoplasia and follicular lymphoma (FL)-like B cells of uncertain significance represent proliferation of Bcl-2/t(14;18)-positive B cells solely in the germinal centres. The condition is interpreted as an early event in the multi-step lymphomagenesis of FL. The aim of this study is to examine the issue more specifically. Methods: We reviewed medical history of FL patients in whom thoracoabdominal surgery with lymphadenectomy had been performed for management of carcinomas. These previously resected lymph nodes as well as the current FL nodes were analysed by immunohistochemistry, fluorescent in situ hybridisation, and PCR amplification with direct sequencing. Results: We studied four such FL patients from a total of 150 patients with FL; all had iFL in the previously resected lymph nodes. Clonal relation was verified and suggested in one case each. The time from lymphadenectomy to the diagnosis of FL was 23–120 months. There appeared to be a reverse correlation between the rate of Bcl-2-positive follicle proliferation and the time from surgery to diagnosis of FL. Conclusions: Although the rate for development of FL in individuals having iFL has been reported to be low from prospective studies, the present data indicate that follow-up studies for a longer period is necessary; the rate of Bcl-2-positive follicle proliferation could be a factor to predict development of FL in prospective studies. Such a retrospective study may contribute to elucidate mechanism(s) involved in lymphomagenesis of FL.